Addition of urea to finishing cattle diets containing steam-flaked corn and wet corn gluten feed - Montgomery, Sean P.; Sindt, J.J.; Farran, T.B.; Pike, N.J.; Coetzer, C.M.; LaBrune, H.J.; Trater, A.M.; Hunter, R.D.; Stock, R.A.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three hundred thirty-nine crossbred beef heifers were used in a 74-day finishing study to evaluate effects of adding 0.5% urea to finishing diets containing steam-flaked corn and 34% (dry basis) Sweet Bran® wet corn gluten feed (WCGF). Diets were fed once daily ad libitum. Urea addition tended (P<0.06) to increase finishing average daily gain, to improve (P<0.12) feed efficiency, and to increase (P<0.06) fat thickness. Heifers fed urea had a lower percentage (P<0.03) of carcasses grading USDA Choice. This study suggests that finishing diets containing a combination of steam-flaked corn and WCGF may benefit from addition of urea as a source of supplemental ruminally available nitrogen.
Keywords: Beef; Wet corn gluten feed; Urea; Finishing